2018
DOI: 10.1021/acs.energyfuels.8b01718
|View full text |Cite
|
Sign up to set email alerts
|

Fast Pyrolysis of Sisal Residue in a Pilot Fluidized Bed Reactor

Abstract: The objective of this research was to study the fast pyrolysis of sisal residue, performed in a pilot unit with a fluidized bed reactor. The tests were carried out by varying the flows of nitrogen (8−14 N m 3 /h), biomass (10.33−25.95 g/ min), and temperature (450−550°C). The experimental planning technique was used to identify the number of tests and the influence of operational variables on the bio-oil yield. One of the highest H 2 /CO (2.16) ratios was found from the eighth test on, which was an appropriate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…Fast pyrolysis reactions were carried out in a pilot-scale fluidized-bed pyrolysis unit, and details of the setup are given in previous papers [39,41]. Before starting the experiments, the silica sand (2.2 kg and di=0.4 mm) was inserted into the reactor (10 L); then, it was preheated by electrical resistances and fluidizing gas up to the reaction temperature defined in the overview of experiments (vide infra).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Fast pyrolysis reactions were carried out in a pilot-scale fluidized-bed pyrolysis unit, and details of the setup are given in previous papers [39,41]. Before starting the experiments, the silica sand (2.2 kg and di=0.4 mm) was inserted into the reactor (10 L); then, it was preheated by electrical resistances and fluidizing gas up to the reaction temperature defined in the overview of experiments (vide infra).…”
Section: Methodsmentioning
confidence: 99%
“…The tests were carried out based on the manipulated variables shown in Table 1. Our group selected the nitrogen gas flow, biomass flow rate, and reaction temperature from an earlier study [39], while the pressure was included as a new investigative element. In another earlier research [41], the pressure was identified as a factor that affects the sisal residue bio-oil viscosity, which may imply a variation in the composition of the bio-oil to a certain extent.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The sisal residue was obtained after processing to obtain sisal fibers and is therefore considered a primary by-product of the sisal fiber production process. This biomass and its biochar were obtained in a fast pyrolysis pilot plant for bio-oil production, with a bubbling fluidized bed reactor [13].…”
Section: Sisal Residue Biochar and Sandmentioning
confidence: 99%